Strategies to Increase Added Value of Agricultural Products through Local Agribusiness Development - Suryaningrum, Dyah Ayu; Lestari, Putu Fajar Kartika (West Science Agro, 2025)
This study explores strategies for increasing the added value of agricultural products through the development of local agribusiness. A qualitative approach was employed, involving in-depth interviews with five key informants, including farmers, an agribusiness practitioner, a cooperative representative, and a local government official. The findings reveal that enhancing product value requires an integrated strategy encompassing product processing and diversification, branding and marketing innovation, technology adoption, farmer empowerment, and policy and institutional support. Farmers’ capacity building, supported by cooperatives and government programs, plays a crucial role in sustaining value-added initiatives. The study concludes that the development of local agribusiness not only increases the competitiveness and marketability of agricultural products but also contributes to rural economic growth and improved community welfare.